Are there sustained psychological impacts in women diagnosed with in-situ or early invasive breast cancers? - Bettina Braun; Bettina Braun; Joke Tio; Barbara Krause-Bergmann; Hans-Werner Hense (Frontiers Media S.A., 2023)
PurposeThe detection of a ductal carcinoma in-situ (DCIS) or an early invasive breast cancer (EIBC), particularly by population-wide mammography-screening-programs, is controversial as an unknown proportion of these cases may be due to overdiagnosis. We investigated whether women with such potentially overdiagnosed breast cancers suffer from sustained adverse psycho-social consequences.MethodsStandardized questionnaires were mailed to 900 survivors, diagnosed with either DCIS or EIBC, requesting self-reports on quality of life using EORTC Quality of Life Questionnaire C-30. Levels of anxiety and depression were assessed using the HADS questionnaires. Item score values in the study group were compared to reference data obtained from normative studies in the German female reference population.ResultsThe 577 women who returned completed questionnaires had a mean age of 65.1 years, 387 (67%) had been diagnosed by mammography screening. Median time since diagnosis was 5.9 years. There were no substantial differences between the study sample and the reference population for most of the items. While most score values were even slightly more favorable in the study group, the scores for cognitive function were moderately lower, especially among younger patients. Score values for anxiety were generally higher among younger women (50 to 59 years) from the study group, while depression scores were lower irrespective of age.ConclusionsThis study indicates that the diagnosis of DCIS or EIBC, which is predominantly a result of screening, does not seem to induce sustained, adverse psychological impacts in affected women when compared with the respective general female population. Only anxiety levels remained elevated among younger women.